Analisis dan Perancangan Pengendali Intensitas Lampu Pijar Jarak Jauh Dengan Sistem Remote control Terhadap Efisiensi Energi - Asih Pitasari Hege; Jauhari Effendi; Bertholomeus Pasangka (Environmental Research Center (PPLH) of Udayana University, 2019)
The light intensity needs to adjust to produce suitability of illumination needs in room based on type of space function so it's possible to save electrical energy. Therefore, creation of energy-efficient lighting is very important so can be controlled. The purpose of this study is analyze and design a light intensity control device with remote control. This type of research is experimental research, which is research that doesn't require a comparison, which means the experiment is given treatment and measurements are made by the tool. The tool designed is a combination of several electronic circuits consisting of power supply, infrared emitting and receiver, digital circuit, relay driver and dimmer circuit. Analysis uses luxmeter as a measure the average light intensity and thermocouple as a measured quality of mean temperature room. The results are light intensity and temperature quality was carried out 3 times at (08.00-12.00 WITA), (12.00-16.00 WITA), (16.00-20.00 WITA) and mean was taken with 9 measurement points with total area of 36 m2 (initial color). The measurement didn't meet the standards of 295 lux and 28ºC, while when being treated it met the room comfort standards of 247 lux and 23ºC. This is due to influence of a tool to control the brightness of the lights. The results of the work are light intensity controller gives 10 stages of resistance values that adjust the brightness of incandescent light with an increasing count, indicating the initial value ranging from 0 to 9.